1987
DOI: 10.1021/ie00062a001
|View full text |Cite
|
Sign up to set email alerts
|

Performance of dual-reactor system for conversion of syngas to aromatic-containing hydrocarbons

Abstract: Cetane number is a measure of ignition quality, specifically ignition delay, of diesel fuel. It is an engine measure of a kinetic phenomena. While it is typically inappropriate to use a thermodynamic measure, such as molecular structure, to predict kinetic behavior, molecular structure does correlate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 6 publications
3
21
0
Order By: Relevance
“…Contrarily, Freitez et al (2011) reported a decrease in cracking activity with a ZSM-5 temperature increase. In addition, the observed effect of maximum selectivity of aromatics at 573 K is in agreement with the results obtained by Varma et al (1985), Varma and Bakhshi (1987), and Karre et al (2013), who also reported an increase of aromatization reactions with a HZSM-5 temperature increase up to 573 K. A negative effect of a HZSM-5 temperature increase was also observed for the selectivity toward CH 4 and C 2 , which increased up to 10.8% and 1.1%, correspondingly. Figure 1 shows the effect of HZSM-5 temperature on the individual product selectivities of DB reaction, C 3 -C 4 paraffins ( Figure 1a) and aromatics ( Figure 1b).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Contrarily, Freitez et al (2011) reported a decrease in cracking activity with a ZSM-5 temperature increase. In addition, the observed effect of maximum selectivity of aromatics at 573 K is in agreement with the results obtained by Varma et al (1985), Varma and Bakhshi (1987), and Karre et al (2013), who also reported an increase of aromatization reactions with a HZSM-5 temperature increase up to 573 K. A negative effect of a HZSM-5 temperature increase was also observed for the selectivity toward CH 4 and C 2 , which increased up to 10.8% and 1.1%, correspondingly. Figure 1 shows the effect of HZSM-5 temperature on the individual product selectivities of DB reaction, C 3 -C 4 paraffins ( Figure 1a) and aromatics ( Figure 1b).…”
Section: Resultssupporting
confidence: 91%
“…The number of studies investigating the combination of FTS and HP in a single reactor is fairly limited. In most, the catalysts' bed configurations evaluated include (a) physical mixture configuration (Martinez et al, 2007;Subiranas, 2009), (b) impregnation of the FT catalyst on the zeolite (Sartipi et al, 2013), (c) coating of the FT catalyst by zeolite (Sartipi et al, 2013), and (d) dual bed (DB) configuration (Varma and Bakhshi, 1987;Gormley et al, 1988;Botes and Böhringer, 2004;Subiranas, 2009;Freitez et al, 2011;Karre et al, 2012;Pabst et al, 2013). The advantages of the DB configuration are (a) operation of FT and HP catalysts at their optimal operation conditions (Asami et al, 2005); (b) no alteration in the activity of the FT catalyst (Karre et al, 2012); and (c) increase in the yield of LPG and aromatics Bakhshi, 1987, Botes andBöhringer, 2004;Cho et al, 2008;Freitez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…83,85 Therefore, the future production of large-volume products such as benzene, toluene, and xylene (BTX) should preferentially be done by further development of catalyst systems able to convert syngas into specific aromatic hydrocarbons. 89,90 Here, black liquor gasification as well as gasification using green biomass are renewable alternatives to the use of coal.…”
Section: Other Aromaticsmentioning
confidence: 99%
“…This approach has been studied for the conversion of wax-containing LTFT products by a number of groups. [74][75][76][77] In these investigations, FTS and co-conversion are not fully segregated. Depending on the level of integration between the two steps (similar operating window or not), it can arguably no longer be considered as co-catalysis during FTS.…”
Section: Co-catalysts For Wax Conversion During Ftsmentioning
confidence: 96%